1986
DOI: 10.1093/schbul/12.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Schizophrenia: A European Perspective

Abstract: Since its inception, the concept of dementia praecox and, later, of schizophrenia has been one of the most disputed entities in modern medicine. Schizophrenia was, and still is, defined by its clinical symptoms and their characteristic evolution over time. No external validating criteria for the diagnosis have been established, in spite of a host of suggestive biological findings, among which the genetic data carry most weight. This absence of clear-cut substrate markers and indicators underscores the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 67 publications
5
49
0
1
Order By: Relevance
“…One possible explanation underlying the long diagnostic and onset diagnosis latency described in this study is that the Swedish tradition is still bound to the seminal concept of Kraepelin [18], which emphasizes the course of the dis ease. This explanation is in accordance with the opinion of Jablenski [19], who described that Scandinavian psychiatry has tradition ally adhered to a 'narrow' concept of schizo phrenia, which is more restrictive than the German one, excluding from its shape not only cases with an admixture of affective fea tures and acute onset (which according to Langfeldt [20] could be classified as schizo phreniform), but also cases of unequivocal paranoid manifestation in which a link could be inferred between the onset and the content of symptoms and a psychotraumatic experi ence. Such cases are classified as reactive psy choses [21][22][23].…”
Section: Discussionsupporting
confidence: 93%
“…One possible explanation underlying the long diagnostic and onset diagnosis latency described in this study is that the Swedish tradition is still bound to the seminal concept of Kraepelin [18], which emphasizes the course of the dis ease. This explanation is in accordance with the opinion of Jablenski [19], who described that Scandinavian psychiatry has tradition ally adhered to a 'narrow' concept of schizo phrenia, which is more restrictive than the German one, excluding from its shape not only cases with an admixture of affective fea tures and acute onset (which according to Langfeldt [20] could be classified as schizo phreniform), but also cases of unequivocal paranoid manifestation in which a link could be inferred between the onset and the content of symptoms and a psychotraumatic experi ence. Such cases are classified as reactive psy choses [21][22][23].…”
Section: Discussionsupporting
confidence: 93%
“…psychopathological symptoms [1], As different psychiatric traditions use divergent symptom Until now, the lack of an etiological defini-sets [2], completed by specific criteria, transna tion of schizophrenia leads to the necessity of tional comparisons lead only to limited concorbasing the schizophrenia diagnosis mainly on dance [3], One important transnational study, the U S-U K study [4], revealed important dif ferences in the usage of the clinical diagnosis of schizophrenia in the United Kingdom and the United States. This study showed that differ ences in incidence between the two countries were largely artifacts of different diagnostic habits and not of different morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Vocational training has improved the situation, but even among newly trained principals in the 1990s, only 40% have completed a postgraduate psychiatry senior house job (Styles, 1991). Each GP will have on their books, on average, around seven people with chronic schizophrenia (Jablensky, 1986), which means that they do not have frequent opportunities to learn about the condition through experience with their own patients. Therefore, GPs need up-to-date information and practical advice on the management of schizo phrenia.…”
Section: Lack Of Training and Experiencementioning
confidence: 99%